2017
DOI: 10.1016/j.jesp.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Configural face processing impacts race disparities in humanization and trust

Abstract: The dehumanization of Black Americans is an ongoing societal problem. Reducing configural face processing, a well-studied aspect of typical face encoding, decreases the activation of human-related concepts to White faces, suggesting that the extent that faces are configurally processed contributes to dehumanization. Because Black individuals are more dehumanized relative to White individuals, the current work examined how configural processing might contribute to their greater dehumanization. Study 1 showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 63 publications
(111 reference statements)
5
40
0
Order By: Relevance
“…The finding that lower SF were more useful with White than Black faces, and that this differential use of information was modulated by implicit racial bias, may be congruent with studies that have revealed that configural processing influences the perceived humanness of a face [65,66]. On the one part, many studies have shown that White individuals have a tendency to dehumanize Black individuals (see [67] for a review).…”
Section: Plos Onesupporting
confidence: 68%
“…The finding that lower SF were more useful with White than Black faces, and that this differential use of information was modulated by implicit racial bias, may be congruent with studies that have revealed that configural processing influences the perceived humanness of a face [65,66]. On the one part, many studies have shown that White individuals have a tendency to dehumanize Black individuals (see [67] for a review).…”
Section: Plos Onesupporting
confidence: 68%
“…Indeed, racial outgroups frequently elicit less configural processing than racial ingroup members (Michel, Rossion, Han, Chung, & Caldara, ; Rhodes, Hayward, & Winkler, ; Tanaka, Kiefer, & Bukach, ). Similarly, neurological data reveal that people are better able to decode the mental states (as measured by the ability to infer emotional states from images of the eye region) of same‐race compared to other‐race targets (Adams et al, ); and, as noted above, disrupting Whites' ability to configurally process Black faces yields particularly negative outcomes (Cassidy et al, ). Similar effects are observed for sexualized women.…”
Section: Faces From Mindsmentioning
confidence: 96%
“…Recent work by Cassidy et al () further extends this configural processing‐to‐mind link while also considering the effects of race. Whereas above, we reviewed evidence suggesting that phenotypically Black faces are ascribed less sophisticated minds, what happens when the human‐like configuration is disrupted as well?…”
Section: Minds From Facesmentioning
confidence: 97%
See 1 more Smart Citation
“…The main conscious emotional concomitants of partial dehumanization, as with prejudice, are hostility and fear. (Schwebel 2003: 66) Rhetoric to the effect that an out-group 'lacks trustworthiness' helps them be seen as subhuman, and, this can escalate a conflict by promoting prejudice and violence (Cassidy et al 2017;Kassin et al 2014). In contrast, the charge of unreliability has not been used to dehumanise in the same way.…”
Section: Ii3mentioning
confidence: 99%